2005
DOI: 10.1007/s10103-005-0347-9
|View full text |Cite
|
Sign up to set email alerts
|

Temperature evolution on human teeth root surface after diode laser assisted endodontic treatment

Abstract: The thermal rise threshold of an 810-nm semi-conductor diode laser on the root surface when used in root canals in vitro for laser assisted root canal treatment is investigated in this study. A total of 50 human single-rooted extracted teeth were included. For this study, the canals were enlarged up to an apical size of ISO#50 file. Laser irradiation was performed with six different settings. Specimens were irradiated at 0.6-1 W output power at the distal end of the fiber and about 1-1.5 W output power in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
1
15

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 14 publications
7
67
1
15
Order By: Relevance
“…Further, Ramsköld et al 30 reported that an increase in temperature could be deleterious to tissues adjacent to the tooth, although elevations of 10 u C for 1 min are still considered safe for periodontal tissue, which is less susceptible to thermal damage than bone tissue because of its high degree of vascularization. 30,31 The temperature increase in magnetic attachments is far below the safety limit of 10 u C. Although this standard covers all medical implants, the increase in this study was below the industrial standard of a maximal temperature increase of 2.0 u C (CENELEC standard prEN45502-2-3), set to limit tissue damage and patient discomfort. Safety of ferromagnetic keepers during MRI Another safety concern is the possible adverse effect of the displacement force acting on the prosthesis owing to the magnetic field.…”
Section: Discussionmentioning
confidence: 80%
“…Further, Ramsköld et al 30 reported that an increase in temperature could be deleterious to tissues adjacent to the tooth, although elevations of 10 u C for 1 min are still considered safe for periodontal tissue, which is less susceptible to thermal damage than bone tissue because of its high degree of vascularization. 30,31 The temperature increase in magnetic attachments is far below the safety limit of 10 u C. Although this standard covers all medical implants, the increase in this study was below the industrial standard of a maximal temperature increase of 2.0 u C (CENELEC standard prEN45502-2-3), set to limit tissue damage and patient discomfort. Safety of ferromagnetic keepers during MRI Another safety concern is the possible adverse effect of the displacement force acting on the prosthesis owing to the magnetic field.…”
Section: Discussionmentioning
confidence: 80%
“…If the number of pulses per second is sufficiently low, and the interval between pulses is sufficiently long to permit delivery of peak powers without exceeding the thermal relaxation time of the irradiated tissue, increased temperature within the tissue may be negligible when compared with the CW emitting the same amount of total energy. 36 In this study, pulse durations of 5, 50, and 500 ms did not affect the bleaching results when the power peak was similar and the same average output power was maintained; therefore, the shortest pulse duration should be preferred. Similarly, the change of duty cycle with same power did not affect the bleaching effect (Fig.…”
Section: # #mentioning
confidence: 69%
“…The rest period between every irradiation cycle in this study was around 10 s. This rest period was proposed by Gutknecht et al [33] and is critical to avoid temperature increases above the safe limit, with the fiber tip being displaced at a speed of approximately 2 mm/s. In the present study, the maximum temperature value in group I at 0.6 W (CW) was 9.83°C, while in group III at 1.2 W and 10 Hz, with a pulse duration of 50 ms and 50% duty cycle, the temperature increase was 9.81°C.…”
Section: Discussionmentioning
confidence: 91%
“…This method has been successfully applied in previous studies [24,31,32]. The fiber was inserted into the root canal up to the apex; then, the irradiation was started, and the fiber was moved in helicoidal movements along the length of the root canal, up to the cervical part at a vertical speed of approximately 2 mm/s [33], i.e., if the length of a root canal was 14 mm, laser irradiation would be applied for 7 s. Between every single irradiation, an adequate rest period was given for the root canal of around 10 s. This time was also needed to carefully reintroduce the fiber back into the root canal.…”
Section: Laser Systemmentioning
confidence: 99%